2021
DOI: 10.1002/bit.27771
|View full text |Cite
|
Sign up to set email alerts
|

Engineered pro‐peptide enhances the catalytic activity of keratinase to improve the conversion ability of feather waste

Abstract: Keratinase is an attractive industrial enzyme that can specifically catalyze keratin waste to obtain value-added products. A challenge to the application of keratinase is improving catalytic capacity to achieve efficient hydrolysis. In this study, we effectively expressed the keratinase gene from Bacillus licheniformis BBE11-1 in Bacillus subtilis WB600 based on pro-peptide engineering. Partial deletion of the pro-peptide sequence and the substitution of amino acid at the pro-peptide cleavage site (P1) suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Identify the Dehairing Ability of Keratinase KerZ1 and Its Damage to Collagen. Given that KerZ1 has shown high keratinase activity (73710.22 U mL −1 , Figure 1A), 15 we selected sheepskin and cowhide with hair to test its dehairing ability and application potential. The results showed that KerZ1 had higher dehairing efficiency for sheepskin.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identify the Dehairing Ability of Keratinase KerZ1 and Its Damage to Collagen. Given that KerZ1 has shown high keratinase activity (73710.22 U mL −1 , Figure 1A), 15 we selected sheepskin and cowhide with hair to test its dehairing ability and application potential. The results showed that KerZ1 had higher dehairing efficiency for sheepskin.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…42 To explore the industrial production potential of the variant strain, fermentation test was carried out on the S100D/Y208V in 3-L bioreactor using a fed-batch strategy based on industrial media. 15 In view of past experience, excessively high glucose concentration will cause the accumulation of byproduct lactic acid, while less carbon source will inhibit cell growth and enzyme production. 43 Therefore, it was appropriate to pump glucose periodically at a constant speed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that point mutation N122Y in keratinase increased the enzymatic activity with an approximately 5.6-fold (liu et al, 2013a ). As the N- and C-termini of a protease may play a regulatory role in the enzymatic activity, swapping these regions with similar domains of enzymes from other bacteria can also result in an enzyme with improved activity and stability (Fang et al, 2016 ; Peng et al, 2021 ).…”
Section: Microbial Degradation Of Keratinmentioning
confidence: 99%
“…Other methods such as PCR-based methods and direct evolution will play a role in obtaining more potent keratinases ( Vidmar and Vodovnik, 2018 ). When the regulatory mechanism of a keratinase is understood, the modification on other regions of the keratinase can also improve its activity and stability ( Fang et al, 2016b ; Peng et al, 2021 ). In a study, the N- and C-terminal regions of KerSMD were replaced with those regions of a homogenous keratinase.…”
Section: Improvement Of Keratinasesmentioning
confidence: 99%